Characterization of Enterovirus Associated m6A RNA Methylation in Children With Neurological Symptoms: A Prospective Cohort Study - Zhu, Danping; Song, Yongling; Hu, Dandan; Li, Suyun; Liu, Guangming; Li, Peiqing; Yang, Sida (Frontiers in Neuroscience, 2021)
Little is known about the particular changes of N6-methyladenosine (m6A) RNA methylation in enterovirus (EV) infection among children with neurologic symptoms. Here, we determined the characterization of EV associated m6A RNA methylation in this population. A prospective cohort study was conducted from 2018/2 to 2019/12 at the Guangzhou Women and Children’s Medical Center. We included EV infected children with and without neurological symptoms. High-throughput m(6)A-RNA immunoprecipitation sequencing (MeRIP-seq) and RNA-seq analysis were used to evaluate the m6A RNA methylation and transcript expression of cerebrospinal fluid samples. The functional annotation and pathways of differentially methylated m6A genes with synchronously differential expression were analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). Seven patients were enrolled in the control group, and 13 cases were in the neurological symptoms (NS) group. A total of 3472 differentially expressed genes and 957 m6A modified genes were identified. A conjoint analysis of MeRIP-seq and RNA-seq data found 1064 genes with significant changes in both the m6A modifications and mRNA levels. The different m6A RNA methylation was increased in the transcriptome’s CDS regions but decreased in both the 3′UTRs and stop codon among the NS group. Functional annotation like the “oxidative phosphorylation” gene pathway, “Parkinson’s disease” and GO terms like “respiratory electron transport chain,” “cellular metabolic process,” and “oxidation-reduction process” was enriched in symptomatic patients. Our study elucidated the changes of RNA m6A methylation patterns and related cellular functions and signaling pathways in EV patients with neurologic symptoms.